Actualization of Bank Principles of Precaution in An Efforts to Protect Customers Against Social Engineering Banking Crime Modes - I Made Aditya Mantara Putra Aditya Mantara (Faculty of Law, Universitas Pekalongan, 2025)
This study is based on the increasing cases of social engineering fraud in the banking sector that threaten customer security. The urgency of this study lies in the need to understand how the bank's precautionary principle can be actualized to protect customers from increasingly sophisticated crime modes. The purpose of this study is to analyze the application of the precautionary principle in customer protection efforts and to identify steps that can be taken by banks to reduce the risk of such crimes. The research method used is a normative method supported by empirical data. Empirical data were collected through in-depth interviews with bank management, namely at PT. Bank BRI Denpasar Renon Branch and PT. Bank BPD Bali Denpasar Branch. The results of the study indicate that although banks have implemented several precautionary principles, there are still gaps in their implementation that can be exploited by criminals. This study found that customer education and improving digital security systems are important steps that need to be taken to strengthen customer protection. The output of this study is expected to provide practical recommendations for banks in optimizing the application of the precautionary principle and increasing customer awareness of the potential risks of social engineering crimes. In addition, the results of this study can also be a reference for better banking policies in protecting customers in the digital era